Microscopic analysis of selected materials used for hot water heating using SEM - Marcek, Lubos; Vavro, Jan; Vavro, Jan (Manufacturing Technology Journal, 2025)
The introduced work deals with the microscopic analysis of metallographically prepared selected metal materials structures, using a scanning electron microscope (SEM). Prepared samples of seamless steel pipes were subjected to a thorough microscopic examination from the outer surface to the inner regions in order to interpret the spe-cific structure, including the change of the inner surfaces due to wear. The experiment showed that the micro-structure and character of the surfaces play a crucial role in the behavior of metallic materials under real condi-tions. Four types of pipes were monitored according to their use. The unused steel pipe (designated as sample No. 1) exhibited a rough outer surface with identified inclusions, while the used pipe (designated as sample No. 2) showed marks of intergranular corrosion and significant wear after long-term use. The older pipe (designated as sample No. 3) showed a decarburized area and inclusions containing sulfides and aluminum. The steel pipe with corrosion layers (designated as sample No. 4) exhibited a continuous corrosion layer with cavitation and cracks. The results of this study offer a comprehensive view relating to the influence of the nature of the micro-structure and wear on the water flow (performance) of metal pipes, with an emphasis on the identification of possible risks associated with geometry change, corrosion and wear. The recommendations create a basis for predicting the degradation as well as appropriate maintenance to ensure their long and reliable service life under real-world conditions of use.
Keywords: Analysis; Microscopic; Structure; Material wear; Pipes